2009
DOI: 10.1021/la9035387
|View full text |Cite
|
Sign up to set email alerts
|

Density Effects on Collapse, Compression, and Adhesion of Thermoresponsive Polymer Brushes

Abstract: We probe, using the Surface Forces Apparatus, the thermal response of poly(Nisopropylacrylamide) (PNIPAM) brushes of various grafting densities, grown from plasma-activated mica by means of surface-initiated polymerization. We thus show that dense thermoresponsive brushes collapse gradually as temperature is increased, and that grafting density greatly affects their ability to swell: the swelling ratio of the brushes, which characterizes the thickness variation between the swollen and the collapsed state, is f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
188
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(212 citation statements)
references
References 54 publications
22
188
2
Order By: Relevance
“…Theoretical predictions for h swell [44,45] allow us to obtain the following expression for the swelling ratio of a brush, as detailed in previous work [24]:…”
Section: B Brush Swelling At Room Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical predictions for h swell [44,45] allow us to obtain the following expression for the swelling ratio of a brush, as detailed in previous work [24]:…”
Section: B Brush Swelling At Room Temperaturementioning
confidence: 99%
“…(i) Surface Plasmon Resonance [16] (SPR) (ii) Quartz-Crystal Microbalance [17][18][19][20][21][22] (QCM) (iii) force measurement techniques such as the Surface Forces Apparatus [23,24] (SFA) or Atomic Force Microscopy [21,22,[25][26][27] (AFM) (iv) Neutron Reflectivity [28][29][30] (NR) (v) in-situ Spectral Ellipsometry [31,32] (SE). While SPR and QCM studies give access to the qualitative evolution of the brush refractive index or effective mass with temperature, force measurements allow the inference of the temperature-dependent brush swelling from the range of steric repulsive forces measured, and only NR and SE (or, equivalently, multi-angle ellipsometry [33] or scanning angle reflectometry [34]) studies can give quantitative insights regarding the evolu-tion of the axial structure of brushes, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the graft density was shown to influence the brush structure. A high graft density can cause phase separation [121], and more generally the density will modulate the protein adsorption rate within the brushes, as for BSA [44]. Malham et al showed that chain rearrangements over time could slightly increase inter-chain adhesion and related this to −NH and C O hydrogen bonding [121].…”
Section: Smart Bio-surfaces: Example Of Poly(n-isopropylacrylamide) Tmentioning
confidence: 99%
“…It is noteworthy that the PNIPAAM brushes may act differently as compared to bulk aqueous solutions since they are constrained by one end to a surface. The dependence of PNIPAAM brush conformation change on different molecular weight and grafting density has been extensively investigated by using a number of experimental techniques including neutron reflectivity (NR), [8][9][10][11] atomic force microscopy (AFM), [12][13][14][15] quartz crystal microbalance measurements (QCM), 12,13,16,17 surface forces, [18][19][20] ellipsometry, 21 water contact angle measurement, 18,19 and surface plasmon resonance (SPR). 22 Generally, the molecular weight and a) Author to whom correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%